PENEGAKAN HUKUM ATAS KETIDAKPATUHAN PERUSAHAAN DALAM MENERAPKAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA - Fadli Akbar; Budi Santoso; Siti Hamidah (Faculty of Law, University of Muhammadiyah Malang, 2019)
PT. Karebet Mas Indonesia Branch of Muara Jawa has mentioned the existence of facilities for personal protective equipment against workers/laborers, but in the implementation of PT. Karebet Mas Indonesia does not all carry out the contents of the agreement and only partially runs for approximately 2 years. The formulation of the problem taken in this reserch is what the obstacles faced by the Manpower and Transmigration Agency of East Kalimantan Province are in enforcing sanctions for companies that do not comply with the occupational health and safety management system. This type of research is empirical juridical with a sociological juridical research approach. The conclusion of this research is the obstacle of the Manpower and Transmigration Office in enforcing the law because the human resources and budgetary funds that do not support and in finding violations of the law on the Manpower and Transmigration Office of East Kalimantan Province are passive.